The 10th anniversary of the uprising: Post the De Doorns strikes how has organising changed for farmworkers in the Western Cape - April, Laverne (Department of Sociology, 2024)
During apartheid farmworkers in South Africa were barred from organising. After the political transition in 1993 labour legislations were extended to farmworkers which included: the Basic Conditions of Employment Act of 1998, the Labour Relations Act 66 of 1995, which extended the right to organise and strike to farm workers; the Extension of Security of Tenure Act 62 of 1997, 2003 a Sectoral Wage Determination that provided a minimum wage level for all agricultural workers. Even though farmworkers were given rights and were protected by the legislation, their working and living situations remained largely unchanged. Thus because of the unchanged working and living condition of farmworkers regardless of the legislation in place, they sparked the uprising in 2012. In De Doorns in 2012-2013 farmworkers organised themselves for the first time in South African history. The farmworkers demanded an increase to their daily wage of R69 to R150, an end to labour brokers and an end to farm evictions, to mention a few. Ten years after the De Doorns uprising, organising farmworkers continues to be a challenge for trade unions. The purpose of this study seeks to ascertain if there has been a change in how trades unions organise seasonal and permanent farm workers. To answer this question, I used purposive sampling and conducted 14 interviews. According to the study's findings, despite inroads made during the 2012-2013 uprising at organising there have been continuities in the way workers organised previously. This is due to internal divisions within the workforce, divisions along ethnicity, nationality, employment status and residence. Trade unions have not been successful in tackling the challenges of organising permanent and seasonal farmworkers and are actively working towards finding alternative ways to organise farmworkers. While there is resistance, it seems on the main workers are still intimidated by paternalistic farmers who hinder attempts to organise farmworkers. The study emphasizes that there are differences in working experiences and organising between local residents and cross-border migrant workers and between seasonal and permanent workers. The study concludes that organising for farmworkers has not change for the betterment because they are divided. However, once all farmworkers; locals and cross-border migrant workers look past their disparate nationalities and forge a shared identity, they will be powerful and capable of organising collectively. Thus, while the farmworkers are still divided, they give the farmers the power to oppress, exploit, marginalised and divide them because the local workers regard the cross-borders migrant workers as their enemies instead of the farmers. I therefore argue that when the workers are united, and see their shared identity, and see what they have in common rather where they differ, they will be better able to organise. Thus, permanent, and seasonal workers can work with their differences and used it productively to create common ground for collective organising and worker power.